Hotspots of Epiphytic Lichen Diversity in Two Young Managed Forests - Peter N. Neitlich; Bruce McCune (Conservation Biology, 1997)
Understanding within‐stand variation in diversity of epiphytes will provide an improved basis for producing timber while conserving biological diversity. Two 80‐ha, 50–year–old managed stands of conifers were surveyed to locate 0.4 ha putative “diversity” plots, the areas appearing most diverse in lichen epiphytes. These plots were generally located in areas made heterogeneous by canopy gaps, wolf trees (trees with large‐diameter lower branches), and old‐growth remnant trees. “Matrix” plots, in contrast, were chosen at random from the remaining, more homogenous forest. Diversity plots hosted from 25% to 40% more epiphytic lichen species than matrix plots in both stands. The strongest within‐stand gradients in species composition were correlated with percentage of plot occupied by gaps and wolf trees. Percentage of the plot in gaps was correlated with species richness (r = 0.79). In the more structurally diverse stand, diversity and abundance of nitrogen‐fixing “cyanolichens” were correlated with percentage of the plot occupied by gaps (0.5